2002
DOI: 10.1111/j.1751-8369.2002.tb00083.x
|View full text |Cite
|
Sign up to set email alerts
|

A 36 Ky record of iceberg rafting and sedimentation from north-west Iceland

Abstract: Evidence from north‐west Iceland's shelf and fjords is used to develop a scenario for environmental change during the last 36 cal Ky. The retreat history of the Iceland Ice Cap during the last deglaciation is delineated through lithofacies studies, carbon analyses and magnetic susceptibility, and studies of ice‐rafted debris (IRD) in sediment cores. Sedimentological data from lake Efstadalsvatn, Vestfirdir peninsula, trace the glacier retreat on land. In two of the high resolution shelf cores we detect near co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 18 publications
4
68
1
Order By: Relevance
“…Relatively warm Atlantic water reached the shelf areas off North Iceland between 18.6-16.3 cal kyrs BP (Table 1;5-6) and the ice sheet retreated from the shelf off West Iceland at 15.0 cal kyrs BP (Table 1;7) (Syvitski et al, 1999;Eiríksson et al, 2000;Andrews et al, 2000;Geirsdóttir et al, 2002). Ingólfsson and Norðdahl (2001) suggested that a rapid rise of global sea level, caused by melting of the large Laurentide, Scandinavian and Barents Sea ice sheets, floated marine based parts of the Icelandic ice sheet and caused its collapse through intensive calving.…”
Section: Bølling Deglaciation and Formation Of Marine Limit Shorelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively warm Atlantic water reached the shelf areas off North Iceland between 18.6-16.3 cal kyrs BP (Table 1;5-6) and the ice sheet retreated from the shelf off West Iceland at 15.0 cal kyrs BP (Table 1;7) (Syvitski et al, 1999;Eiríksson et al, 2000;Andrews et al, 2000;Geirsdóttir et al, 2002). Ingólfsson and Norðdahl (2001) suggested that a rapid rise of global sea level, caused by melting of the large Laurentide, Scandinavian and Barents Sea ice sheets, floated marine based parts of the Icelandic ice sheet and caused its collapse through intensive calving.…”
Section: Bølling Deglaciation and Formation Of Marine Limit Shorelinesmentioning
confidence: 99%
“…Truncated shorelines also suggest that there was a Younger Dryas expansion of glaciers in West Central Iceland and along the southern (Breiðafjörður) perimeter of Northwest Iceland (Norðdahl and Pétursson, 2005). Sediment cores retrieved from the Ísafjarðardjúp basin in Northwest Iceland reveal expansion of glaciers into the trunk fjord (Geirsdóttir et al, 2002). Promontories along the western and north-eastern coast of Northwest Iceland remained mostly ice-free at the same time (Hjort et al, 1985).…”
Section: The Younger Dryas Glacial and Climatic Eventmentioning
confidence: 99%
“…After the glacier retreat at the end of the Younger Dryas, the glacial fronts re-advanced again in the Early Preboreal period, around 11.2 ka (Ingólfsson et al, 1997;Norðdahl and Einarsson, 2001;Norðdahl and Pétursson, 2005). Later, the glaciers retreated rapidly (Kaldal and Víkingssson, 1990;Andrews et al, 2000;Norðdahl and Einarsson, 2001;Geirsdóttir et al, 2002Geirsdóttir et al, , 2009Larsen et al, 2012). By 10.2 ka the centre and north of Iceland was already deglaciated (Stötter et al, 1999;Caseldine et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…During the Allerød stadial, the temperature rose again considerably and the glaciers retreated again (Rundgren, 1995(Rundgren, , 1999Rundgren and Ingólfsson, 1999). During the Younger Dryas the glaciers started to re-advance and in the north and northwest they reached the present coastline and entered the great fiords, in many cases obstructing lateral valleys and forming lakes (Geirsdóttir et al, 2002;Norðdahl and Pétursson, 2005), but many interfluves remained free of ice during this period (Norðdahl and Einarsson, 2001). After the glacier retreat at the end of the Younger Dryas, the glacial fronts re-advanced again in the Early Preboreal period, around 11.2 ka (Ingólfsson et al, 1997;Norðdahl and Einarsson, 2001;Norðdahl and Pétursson, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…2, part A) was collected from the center of a large sediment drift in Djúpáll Trough (Geirsdóttir et al, 2002;Ólafsdóttir, 2004) that extends from Ísafjardardjúp to the shelf break adjacent to Denmark Strait (Labeyrie et al, 2003;Andrews et al, 2009a;Ólafsdóttir et al, 2010). The site of core 2263 lies beneath the axis of the warm IC.…”
Section: Sediment Coresmentioning
confidence: 99%